2015
DOI: 10.1017/etds.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal analysis of ergodic averages in some non-uniformly hyperbolic systems

Abstract: Abstract. This article is devoted to the study of the multifractal analysis of ergodic averages in some nonuniformly hyperbolic systems. In particular, our results hold for the robust classes of multidimensional nonuniformly expanding local diffeomorphisms and Viana maps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Barreira-Schmeling [11]. Recently Zhou and Chen [65] have show that the set of historic points carries full topological pressure for systems with non-uniform specification under certain conditions; this has been generalized by Tian-Varandas [63]. Here we have shown that wild historic points are generic in a broad class of examples.…”
Section: Conjecturessupporting
confidence: 51%
“…Barreira-Schmeling [11]. Recently Zhou and Chen [65] have show that the set of historic points carries full topological pressure for systems with non-uniform specification under certain conditions; this has been generalized by Tian-Varandas [63]. Here we have shown that wild historic points are generic in a broad class of examples.…”
Section: Conjecturessupporting
confidence: 51%
“…We must mention that the case r = 1 was proved in [15]. However, unlike we do here, in that article the proof is not based on the saturadness.…”
Section: Introductionmentioning
confidence: 77%
“…For Banach valued continuous observable, similar variational principle was also established for system with specification property [11]. As a generalisation of above variational principle, the variational principle regarding topological pressure of M ϕ,α was also established for systems we mentioned above [26,34,40]. Meanwhile, for the above systems, the measure negligible set I ϕ carries full topological pressure [35][36][37].…”
Section: Introductionmentioning
confidence: 90%